KH. M. Bisri Syansuri dan Pembaruan Pesantren - Ulum, M Bustanul (FALASIFA : Jurnal Studi Keislaman, 2017)
ABSTRACTAs an institution, boarding school also experienced its own dynamics. They makelimited reforms in the education system in order to always be able to adapt tochanging times. KH. Bisri Syansuri, as a founder and caretaker of boarding schoolMambaul Maarif Denanyar Jombang, make improvements periodically so thatestablished educational institutions can balance the dynamics of the times. Thearticle below discusses the work of Kiai Bisri as a reformer in the field ofeducation.Keyword: KH. Bisri Syansuri, Educational Reform, System Improvement